IMPLEMENTASI ALGORITMA WELCH-POWELL PADA PEWARNAAN GRAF WILAYAH DI KALIMANTAN TIMUR - Nur Aulia, Shofinatul Wahdah; Inayah, Jauharotul; Imron, M.; Fanani, Aris (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
Graph theory is a branch of mathematical study that studies the relationship of a non-empty set which contains several elements called vertices and a list of paired elements called edges. Graph coloring is a technique of adding color to every point on a graph. The purpose of this study is to make it easier for map readers to distinguish each region on a map of East Kalimantan Province. This study implements graph coloring using the Welch-Powell algorithm method which colors the graph based on the highest degree of the end point. This study resulted in graph coloring on the East Kalimantan map obtaining a chromatic number X(G) = 3 in red for the Kutai Kartanegara, Paser, and Berau regions, then blue for the North Penajam Paser, Mahakam Ulu, Botang, and Samarinda regions, and the color green for West Kutai, East Kutai and Balikpapan.